1990
DOI: 10.1177/004728759002800301
|View full text |Cite
|
Sign up to set email alerts
|

Rural Resident Tourism Perceptions And Attitudes By Community Level Of Tourism

Abstract: Focusing on the residents of 28 rural Colorado communities, this research examines differences in resident tourism perceptions and attitudes across communities categorized on the basis of the community's existing level of tourism. The results indicate that the perceived impacts of tourism, both positive and negative, increase with increasing levels of tourism. With respect to resident attitudes toward additional tourism development, however, the results suggest that resident attitudes initially increase in fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
199
5
28

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(248 citation statements)
references
References 22 publications
16
199
5
28
Order By: Relevance
“…These findings were supported in previous studies such as by Gursoy and Rutherford (2004) and Purdue, Long and Allen (1990) that mega events generate and improve the local economy as well as promoting more business for local people (Cheng & Jarvis, 2010, Nunkoo & Ramkisoon, 2011.…”
Section: Economic Benefits Of the MC To The Communitysupporting
confidence: 85%
“…These findings were supported in previous studies such as by Gursoy and Rutherford (2004) and Purdue, Long and Allen (1990) that mega events generate and improve the local economy as well as promoting more business for local people (Cheng & Jarvis, 2010, Nunkoo & Ramkisoon, 2011.…”
Section: Economic Benefits Of the MC To The Communitysupporting
confidence: 85%
“…However, it has also been criticized on the ground that communities are heterogeneous with different interests and that their attitudes depend on many factors. Nevertheless, it remains the single most cited refereed article in tourism studies [40] that "provides a useful framework for description and interpretation" [41].…”
Section: Perceived Tourism Impacts and Stage Of Destination Developmentmentioning
confidence: 99%
“…A public good, by its very nature, is a candidate for government activity, since "the benefits from a public or social good, unlike those from a purely private good, are seen to involve external consumption effects on more than one individual" (Samuelson and Scott 1975:144). Hence, destination residents may be less willing to support additional tourism development through local revenue tax funds (Long, Perdue and Allen 1990) and could favor government control over development (Allen, Hafer, Long and Perdue 1993). The local authorities have the delicate task of juggling private sector interests with local resident needs and wants, in order to maintain the economic health of the community and ensure that development is sustainable.…”
Section: The Nature Of Community Tourism Destinationsmentioning
confidence: 99%
“…Some studies on rural communities have demonstrated predominantly positive perceptions of tourism development's impact on the local economy (Allen et al 1993). However, research by Long et al (1990) on 28 rural Colorado communities indicated that residents' favor of tourism development increased initially, but became less favorable after a threshold level of development was reached. As well, longitudinal study by Getz (1994) showed that resident support for tourism was linked to perceptions of benefits outweighing the costs of tourism development; this supported Ap's (1992) contention that social exchange theory can help explain resident attitudes.…”
Section: Diverse Community Viewsmentioning
confidence: 99%